DOGME ELT: THE POSSIBILITY TO USE THE APPROACH TO STUDENTS IN HIGHER EDUCATION - Yanti, Gina Selvira (Jurnal Pembelajaran Prospektif, 2018)
Despite the changes in language teaching approach from years ago until this day, it seems that students’ low capability to use English communicatively has been a crucial issue for most EFL students. Thus, this phenomenon still encourages educators and researchers to keep on searching for a language teaching approach that can be called as a perfect approach. In the search of socalled perfect language teaching approach, there have been many teaching approaches such as grammar-translation method, audio lingual method, and communicative language teaching that have been used and implemented by teachers/educators around the world. Even until today, those teaching approaches are still considered as teachers’ / scholars’ favorite. Then, in the early 2000, Scott Thornbury presented his own innovation of a teaching approach that called Dogme approach. He emphasized that teaching language is not as effective as before because most of teachers, nowadays, have been strictly attached to course books or textbooks in their teaching that makes the main goal to set up a real communicative atmosphere among learners is not achieved. He claims that in a classroom, there should be only teacher and learners. Then, this paper aims to describe about what is Dogme in ELT, its application, its criticism and the possibility to use this approach in Indonesian context.